Hubungan Dukungan Keluarga dan Self Management dengan Kepatuhan Minum Obat Pasien Hipertensi di Rumah Sakit Imelda Pekerja Indonesia - Eka Nugraha V. Naibaho; Hamonangan Damanik; Edisyah Putra Ritonga; Ratna Dewi; Lawrencea Perdana Faustina (Yayasan Literasi Sains Indonesia, 2022)
Hypertension can cause the risk of damage to the cardiovascular, brain and kidneys, causing complications from several diseases, such as stroke, myocardial infarction, kidney failure and heart failure. Family support and compliance in hypertensive patients have a very strong correlation and have a positive direction. Self-management is thought to have caused a large increase in cases of non-communicable diseases in Indonesia, including hypertension. The aim of the research is to determine the relationship between family support and self-management with medication adherence for hypertensive patients at the Imelda Workers Indonesia Hospital in 2022. This type of quantitative research uses a cross-sectional approach. The research was carried out at the Imelda Indonesian Workers Hospital in Medan in June-July 2022. The study population was 64 hypertensive patients. The research sample used total sampling so the total sample was 64 people. Bivariate analysis used the Chi Square Test assisted by SPSS 22 software. Research results: The majority of family support for hypertensive patients was in the moderate category (45-60) with 30 people (46.9%). Family support was in the moderate category (45-60) with non-compliance with taking medication (8-11) in 16 hypertensive patients with a P.Value of 0.762>0.05, meaning that there was no relationship between family support and compliance with taking medication in hypertensive patients. The majority of self-management in hypertensive patients is in the sufficient self-management category (45-60) as many as 37 people (57.8%). Self Management was sufficient (45-60) with non-compliance with taking medication (8-11) in 19 hypertensive patients with a P.Value of 0.107>0.05, meaning that there was no relationship between Self Management and compliance with taking medication in hypertensive patients.